The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1590/s0100-55022006000200002
|View full text |Cite
|
Sign up to set email alerts
|

Disseminação seletiva da informação na área da saúde: o caso do web site Amedeo

Abstract: Ciência da Informação. RESUMOAs atividades de produção/divulgação de informações foram otimizadas pela facilidade de comunicação oferecida pela internet, e a produção científica cresce cada vez mais. Com foco nas facilidades de acesso à informação científica oferecidas pela tecnologia, o objetivo é evidenciar os benefícios da aplicação da Disseminação Seletiva da Informação (SDI) na formação de profissionais da saúde, a partir da análise do web site Amedeo. Faz-se um estudo comparativo, de modo a verificar com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(14 reference statements)
0
1
0
1
Order By: Relevance
“…(30) The Brazilian Federal Medical Council reported that 95% of physicians in southeastern Brazil, answering to a survey, informed that they needed to update their knowledge, and 83% needed to improve their technical qualifications. (25) This study demonstrated that physicians in intensive care units seek professional updates using the internet and scientific events.…”
Section: Continued Education and Researchmentioning
confidence: 99%
“…(30) The Brazilian Federal Medical Council reported that 95% of physicians in southeastern Brazil, answering to a survey, informed that they needed to update their knowledge, and 83% needed to improve their technical qualifications. (25) This study demonstrated that physicians in intensive care units seek professional updates using the internet and scientific events.…”
Section: Continued Education and Researchmentioning
confidence: 99%
“…Souto (2006) sugere que a Ciência da Informação exerce um papel importante na atualização dos profissionais da área da saúde, enquanto instrumento para a educação continuada, e evidencia os benefícios de se aplicar a Disseminação Seletiva da Informação na formação de profissionais da saúde. Lopes (2000, p.285) declara que a MBE se traduz pela prática da medicina em um contexto em que a experiência clínica é integrada com a capacidade de analisar criticamente e aplicar racionalmente a informação científica de forma a melhorar a qualidade da assistência médica.…”
Section: A Competência Informacional/information Literacyunclassified